Autogenous and drying shrinkage properties of precast recycled aggregate concrete - Ningxu Zhang; Qing Yang; Dapeng Li; Yong Yu; Xiaoyu Jiang; Jinjun Xu (Case Studies in Construction Materials)
Crushing prefabricated rejects into recycled aggregates (PRAs) and recasting them forms precast recycled aggregate concrete (PRAC), which offers superior mechanical properties, durability, and cost and environmental benefits compared to conventional RAC. However, limited research on its shrinkage characteristics hinders its practical use in engineering. This paper thus provides a comprehensive analysis of the autogenous and drying shrinkage properties of PRAC through experimental and theoretical methods. It first explores the effects of factors like water-to-cement ratio, PRA replacement rates, PRA’s parent concrete strength and mixing techniques on ultimate shrinkage strains and dimensionless strain-age curves. Predictive models for autogenous and drying shrinkage of PRAC are then developed based on the results. Key findings include: (i) The addition of PRAs alters shrinkage behavior, typically reducing autogenous shrinkage strain ultimate values and increasing drying shrinkage strain ultimate values, with finer PRAs having a greater impact than coarser ones. (ii) Raising the strength grade of the PRA's parent concrete minimally affects autogenous shrinkage but significantly reduces drying shrinkage. (iii) The two-stage mixing method has minimal effect on shrinkage strain, while the equivalent volume mortar method significantly reduces both autogenous and drying shrinkage. (iv) The predictive models for autogenous and drying shrinkage demonstrate high accuracy and safety.